CDIO – Break Through Solution For Highter Education Viet Nam - Nguyễn, Thị Thanh Liên (Đại học Quốc gia Thành phố Hồ Chí Minh, 2016)
With the goal of innovation and comprehensive basic on higher education in Vietnam towards standardization, modernization, and international integration, the action program of the Ministry of Education and Training in the period 2011 - 2016 , issued together with Decision No. 1666/QD-BGDDT May 4, 2012, emphasized the central issue is "training the social needs" to solve the supply - demand for human resources in the university training, human resource needs for national development, contributing actively to the implementation of economic growth under the new model, increasing labour productivity, improve efficiency, environmental protection and sustainable development. In the context of international integration over the years, the higher education in Vietnam go after a real long steps. Therefore, the critical issue is the school set out to move from "just what they are trained" to "what social training needs", to gradually narrow the gap between school and home use. Thus, to determine based on the standard output to design input, program content and training plans accordingly. The key to solving that's innovation performance of the CDIO model, students are trained to follow a scientific process and the comprehensive development of knowledge, skills and attitudes, "product" of higher education to meet the increasing requirements of the labor market, creating a foundation for striving to 2020, Vietnam has a system of advanced education, access to international standards. This paper for analysis of the necessity and reality orientation apply CDIO model - innovative solutions for higher education reform in Vietnam under the action plan period 2011 - 2016 of Ministry of Education and Training.